PROFESSIONALLY ORIENTED RUSSIAN LANGUAGE INSTRUCTION FOR AGRARIAN UNIVERSITY STUDENTS IN THE CONTEXT OF DIGITAL TRANSFORMATION AND GENERATIVE ARTIFICIAL INTELLIGENCE (American Journal of Interdisciplinary Research and Development, 2026)
The modernization of agrarian higher education requires a language curriculum that does not treat Russian as an isolated philological subject, but as a professionally functional instrument of disciplinary communication, access to scientific literature, mediated interaction, workplace documentation, and intercultural cooperation. At the same time, the rapid spread of digital learning environments and generative artificial intelligence has changed not only the technical means of instruction, but also the logic of course design, the teacher’s role, the student’s agency, and the architecture of assessment. Against this background, the present study aims to develop a scientifically grounded model of professionally oriented Russian language instruction for agrarian university students that integrates action-oriented language pedagogy, CEFR-based mediation, agrarian terminology, hybrid and multimodal learning, and human-centered AI use. Methodologically, the study is based on an integrative analytical design that synthesizes international normative and methodological documents, digital-education frameworks, AI-competency models, and regional studies on Russian-language teaching in agrarian and non-linguistic universities. The analytical corpus includes UNESCO publications on generative AI and AI competency frameworks, the Council of Europe’s CEFR Companion Volume, OECD analytical reports on digital transformation and AI in education, FAO materials on digital agricultural learning, and a set of scholarly works devoted to terminology, speech culture, motivation, and digital linguodidactics in Russian-language instruction. The study’s main result is the formulation of the AGRARIAN model of course design, which consists of eight mutually reinforcing components: Action-oriented curriculum logic, Genre-based progression, Russian terminological core, AI-assisted personalization, Reflective and ethical regulation, Interdisciplinary case practice, Assessment ecosystem, and Networked hybrid learning. The article demonstrates that the pedagogical effectiveness of Russian-language instruction in agrarian universities depends not on the simple addition of digital tools, but on the restructuring of the whole didactic system: objectives must be competence-based, content must be professionally meaningful, tasks must simulate real agrarian communication, assessment must combine formative feedback with authentic performance indicators, and AI must remain subordinate to teacher judgment, disciplinary goals, and ethical safeguards. The scientific novelty of the article lies in the conceptual integration of agrarian professional discourse, Russian-for-specific-purposes methodology, CEFR mediation, and AI literacy into a single higher-education model applicable to multilingual and digitally transforming university settings. The theoretical significance of the study consists in clarifying the structure of professionally oriented Russian-language competence for agrarian students, while its practical significance lies in offering a directly implementable framework for curriculum revision, module planning, task design, and assessment in agrarian higher education.